The Overlooked Role of Roadworks in Micromobility’s Accessibility - Dimitrios Argyros; Jeppe Rich; Anders F. Jensen (Findings)
Transforming cities often comes with the overlooked consequence of roadworks. Complex underground infrastructure, such as cabling, anti-flooding systems, and heating works, makes urban transformations costly and time-consuming. This trend will likely persist, making it important to understand its impact on our daily lives. For the first time, we present a comprehensive dataset on construction work in Copenhagen and analyse travel time delays in cycling trips by expanding a cycling speed model based on extensive trajectory data. Our findings reveal that construction activities can reduce average cycling speeds by 0.4 to 1 km/h on affected segments, significantly affecting mobility.